Peningkatan Tata Kelola SDM bagi UMKM di Era Digital di Tajaul Karomah Desa Situgadung Kabupaten Tangerang - Guruh, Muhamad; Syatoto, Iman; Harras, Hadyati (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic development of rural communities. However, many MSMEs still face challenges in managing human resources (HR) effectively, especially in adapting to the demands of the digital era. This community service program (PKM) aimed to enhance human resource governance among MSMEs under the Tajaul Karomah group in Situgadung Village, Tangerang Regency. The main objective was to equip participants with the knowledge and skills necessary to manage HR efficiently and leverage digital tools to improve productivity and competitiveness. The PKM activity was conducted on April 4–5, 2025, by 12 lecturers from Universitas Pamulang and involved 30 participants from the local community. The method of implementation included planning, execution, and reporting stages. Activities were carried out through material presentations, hands-on practice, group discussions, and interactive Q&A sessions. The results showed a significant increase in participants' understanding of HR management principles and digital adaptation strategies. Participants expressed strong interest in applying the acquired knowledge to their business operations. This PKM initiative has contributed positively to local MSME development and demonstrated the importance of academic-community collaboration in addressing socio-economic challenges.